The Complex Epidemiology of Carbapenem-Resistant Enterobacter Infections: A Multicenter Descriptive Analysis. (November 2015) - Lazarovitch, Tsilia; Amity, Keren; Coyle, Joseph R.; Ackerman, Benjamin; Tal-Jasper, Ruthy; Ofer-Friedman, Hadas; Hayakawa, Kayoko; Bogan, Christopher; Lephart, Paul R.; Kaplansky, Tamir; Maskit, Moran; Azouri, Tal; et al.
Abstract : BACKGROUND: The pandemic of carbapenem-resistant Enterobacteriaceae (CRE) was primarily due to clonal spread of bla KPC producing Klebsiella pneumoniae . Thus, thoroughly studied CRE cohorts have consisted mostly of K. pneumoniae . OBJECTIVE: To conduct an extensive epidemiologic analysis of carbapenem-resistant Enterobacter spp. (CREn) from 2 endemic and geographically distinct centers. METHODS: CREn were investigated at an Israeli center (Assaf Harofeh Medical Center, January 2007 to July 2012) and at a US center (Detroit Medical Center, September 2008 to September 2009). bla KPC genes were queried by polymerase chain reaction. Repetitive extragenic palindromic polymerase chain reaction and pulsed-field gel electrophoresis were used to determine genetic relatedness. RESULTS: In this analysis, 68 unique patients with CREn were enrolled. Sixteen isolates (24%) were from wounds, and 33 (48%) represented colonization only. All isolates exhibited a positive Modified Hodge Test, but only 93% (27 of 29) contained bla KPC . Forty-three isolates (63%) were from elderly adults, and 5 (7.4%) were from neonates. Twenty-seven patients died in hospital (40.3% of infected patients). Enterobacter strains consisted of 4 separate clones from Assaf Harofeh Medical Center and of 4 distinct clones from Detroit Medical Center. CONCLUSIONS: In this study conducted at 2 distinct CRE endemic regions, there were unique epidemiologic features to CREn: (i) polyclonality, (ii) neonates accounting for more than 7% of cohort, and (iii) high rate of colonization (almost one-half of all cases represented colonization). Since false-positive Modified Hodge Tests in Enterobacter spp. are common, close monitoring of carbapenem resistance mechanisms (particularly carbapenemase production) among Enterobacter spp. is important. Infect. Control Hosp. Epidemiol. 2015;36(11):1283–1291